A tool for screening potentially inappropriate prescribing in Chinese children - Li, Siyu; Huang, Liang; Zeng, Linan; Yu, Dan; Jia, Zhi-Jun; Cheng, Guo; Zhang, Lingli (Frontiers in Pharmacology, 2022)
Background: More than half of adverse drug events in pediatric patients are avoidable and blocking medication errors at the prescribing stage might be one of the most effective preventive measures. Objective: To form a tool (a series of criteria) for detecting potentially inappropriate prescriptions in children, promote clinical rational drug use and reduce risks of medication in children. Methods: Potentially inappropriate prescription propositions for children were collected through a systematic review. Then, the Delphi technique was adopted to form the final criteria. Panelists were asked to use a 5-point Likert scale to rate their agreement with each potentially inappropriate prescription proposition and were encouraged to add new propositions based on their clinical experience and knowledge. After 2 rounds of Delphi survey and propositions were fully revised and improved, the final criteria for identifying potentially inappropriate prescriptions in children were formed. Results: The final criteria for identifying potential inappropriate prescriptions in children has 136 propositions, which were divided into “criteria for children with non-specific diseases/conditions” (71 propositions: 68 for potentially inappropriate medication, 3 for potential prescribing omission) and “criteria for children with specific diseases/conditions” (65 propositions: 55 for potentially inappropriate medication, 10 for potential prescribing omission), according to whether the proposition was about identifying specific risks associated with one drug in children with a specific other diseases/conditions that do not exist in children with other diseases/conditions. Conclusion: A tool for screening potentially inappropriate prescriptions in children is formed to detect potentially inappropriate medication and prescribing omission in pediatrics and is available to all medical professionals liable to prescribe or dispense medicines to children.